A channeled 3D structure of a new polyoxometalate-based triiron(III) cluster: Synthesis, crystal structure and electrochemical properties. (7th July 2017) - Dhifallah, Fatma; Belkhiria, Mohamed Salah; Leclerc, Nathalie; Parent, Loic; Mbomekalle, Israel-Martyr; Cadot, Emmanuel
Graphical abstract: A novel and interesting hybrid compound based on Wells-Dawson polyanion and triiron macrocation was synthesized and characterized. This compound has a tridimensional structure with nanoscale channels running parallel to the c-axis and filled with crystallization water molecules. Abstract: Tripotassium-tris[(µ3 -oxido)triaqua-hexakis(acetato)triiron(III)](octadecatungsto-diphosphato(V))ditriacontahydrate, K3 [Fe3 O(CH3 COO)6 (H2 O)3 ]3 [P2 W18 O62 ]·32H2 O (1 ) is constructed from Wells–Dawson type polyanion [α-P2 W18 O62 ] 6− and triiron(III) cluster cations [Fe3 O(CH3 COO)6 (H2 O)3 ] + which are assembled by potassium ions to form a supramolecular structure with nanoscale tunnels running parallel to the c -axis. The structure was confirmed by single crystal X-ray analysis, FT-IR, 1 H and 31 P NMR and UV–Vis spectroscopy studies, cyclic voltammetry and TGA-DSC thermal analyses. Compound1 crystallizes in the monoclinic space group P 21 / n with cell parameters: a = 17.81830(10) Å, b = 29.6939(3) Å, c = 29.7691(2) Å, β = 91.4700 (10)° and Z = 4.